REGRESSION-BASED MODELLING OF COMPRESSIVE STRENGTH OF RICE HUSK ASH–LATERITIC COMPRESSED EARTH BLOCKS USING LINEAR, INTERACTION, AND POLYNOMIAL REGRESSION MODELS (NAU Journal of Technology and Vocational Education, 2026)
incorporating rice husk ash (RHA) as a partial cement replacement. While previous studies have examined the effect of RHA on stabilised soils, limited research has applied regression-based modelling to quantify the combined effects of RHA content, stabiliser dosage, and curing age. A total of 18 mix combinations were prepared with RHA replacement levels of 0 - 40% and stabiliser contents of 6% and 10%. Compressive strength was evaluated at 7, 28, and 90 days in accordance with standard testing procedures using a universal testing machine. Linear, interaction, and polynomial regression models were developed, and model performance was assessed using R², adjusted R², RMSE, and MAPE. Results show that the interaction model achieved the best balance between accuracy and interpretability (R² = 0.91; adjusted R² = 0.89), while the polynomial model showed higher apparent accuracy (R² = 0.96) but signs of overfitting. Sensitivity analysis revealed that RHA exhibits a strong nonlinear influence on compressive strength, with a sensitivity index of 22.8 for the quadratic term. The study is limited by a relatively small dataset and the absence of external validation. However, the developed models provide a useful predictive framework for optimising stabilised lateritic blocks and reducing cement consumption.
Keywords: Rice husk ash; Compressive strength; Lateritic Soil Stabilisation; Supplementary cementitious materials; Sensitivity analysis